Koping Pada Anak - Nani Nurhaeni (Jurnal Keperawatan Indonesia, 1998)
Kegagalan koping pada anak bias mempengaruhi proses tumbuh kembang anak terutama dari aspek psikologis. Factor-faktor yang bias mempengaruhi kemampuan koping anak perlu diperhatikan baik dari aspek anak itu sendiri maupun dari lingkungan. Hal ini untuk mendukung anak secara konstruktif dalam menghadapi stress yang muncul. Jenis stressor yang muncul sangat mempengaruhi koping anak. Respon yang diperlihatkan anak sangat bervariasi tergantung dari tingkatan usia (tumbuh kembang), persepsi dan reaksi anak serta dukungan dari orang tua. Seorang perawat sangat penting untuk menguasai pengetahuan tentang koping anak guna menyelesaikan anak baik di lingkungan rumah, lingkungan rumah sakit ataupunÂ  di masyarakat, sehingga bias melakukan koping secara konstruktif.Â AbstractA coping failure in a child may psychologically influence his or her growth and developmental process. Many factors can play a role in an ability of child to cope with problems, specifically factors from the child and from the environment. In addition, types of stressor can affect the pattern of a child coping mechanism. To oversee factors may support a child to cope constructively with the stressors. Fear, loss, and death are normal stressors for a child. A child may demonstrate a variety of respons to deal with the stressors depend on the level of age (related to a growth and development process), child perception and reaction, and parenteral supports. A nurses is in a well prepared position to assist a child in dealing with problems at home, school environment, hospital or community, so the child will be able to cope positively.Keywords: Coping process, child stressors, child attitude and behavior related responses, support system, defense mechanism.